Adoption of Qris (Quick Response Code Indonesian Standard) through a Strategy to Increase the Financial Literacy of UMKM Players in the City of Solo - Sari, Ita Purnama (PT FORMOSA CENDEKIA GLOBAL, 2024)
QRIS (Quick Response Code Indonesian Standard) is a QR code standard developed to facilitate online payment transactions in Indonesia. QRIS as a new online payment method and the low financial literacy of the people of Solo City are two significant challenges in adopting QRIS. This research aims to identify effective strategies in increasing the financial literacy of UMKM in Solo City through adopting QRIS as an online payment method. The method used in this research is qualitative descriptive analysis with a case study type of research. This research was conducted in Solo City. The research results that the author obtained were that micro business actors in Solo City still have limited understanding of the use of QRIS, including understanding the use of technology and understanding transactions. The strategy carried out by Bank Indonesia Solo City to increase financial literacy through the adoption of QRIS is by providing outreach and education through FEKDI events, ADIPATI Festival, KENDUREN UMKM, SYEKATEN, Solo Great Sale (SGS) and onboarding UMKM, collaborating and providing training for UMKM. The strategies for increasing literacy that should be carried out are based on the SWOT analysis that has been carried out, namely increasing awareness of financial literacy through education and outreach, helping the growth of small and medium businesses, educating on the use of smartphone media and developing the QRIS ecosystem.